CHOICE OF ALTERNATIVE MONOTHERAPY IN EPILEPSY - I. Ju. Kovaleva (Эпилепсия и пароксизмальные состояния, 2016)
Every neurologist or epileptologist faces a problem of changing antiepileptic treatment. The goal of the therapy is producing seizure freedom. Many patients fail a first drug due to lack of efficacy or failure to tolerate an initial medication. While monotherapy is preferable in epilepsy treatment we need an alteration in therapy. The preferred method for converting between the first and the second therapy is transitional polytherapy, a process involving initiation of a new antiepileptic drug (AED) and adjuncting it toward a target dose while maintaining or reducing the dose of the baseline medication. This articale reviews practical consensus recommendations from an expert panel for successful monotherapy to monotherapy AED conversions are then summarized. Transitional polytherapy is most successful when clinicians appropriately manage the titration strategy and consider pharmacokinetic factors germane to the baseline and new adjunctive medication.